Anticonvulsant activity of aqueous fraction of Carissa edulis root bark. (September 2015) - Ya'u, J.; Yaro, A. H.; Malami, S.; Musa, M. A.; Abubakar, A.; Yahaya, S. M.; Chindo, B. A.; Anuka, J. A.; Hussaini, I. M.
Abstract Context: Carissa edulis Vahl (Apocynaceae) is used in Nigerian folk medicine to manage a plethora of diseases including epilepsy, cancer, and inflammation; its efficacy is widely acclaimed among communities of northern Nigeria. Objective: This study establishes anticonvulsant activities of aqueous fraction of ethanol root bark extract of Carissa edulis (RAF) and sub-fractions (S1 and S2) in animal models. Materials and methods: We evaluated the acute toxicity of the RAF, S1 and S2, and the anticonvulsant activity using pentylenetetrazole (PTZ), picrotoxin, strychnine, N-methyl-d-aspartate (NMDA), isoniazid (INH), and aminophylline-induced seizures in mice. Their effects on maximal electroshock (MES) and kindling-induced seizures were studied in chicks and in rats, respectively, and in the electrophysiological study. The doses used for RAF were 150, 300, and 600 mg/kg while S1 and S2 were 250, 500, and 1000 mg/kg. Both RAF and sub-fractions were administered once during the experiment. Results: The intraperitoneal LD50 of the RAF was estimated to be 2222.61 mg/kg and that of the S1 and S2 were above 5000 mg/kg. RAF protected the mice by 50% while sub-fractions by 16.67% against PTZ-induced seizures. RAF offered 33.33 and 16.67% protection against strychnine and NMDA models, respectively. However, RAF offered 66.67–33.33% protections against aminophylline-induced seizures at doses of 150 and 600 mg/kg, but RAF, S1, and S2 had no effect on MES-induced seizures. Discussion and conclusion: Our results validate the use of the plant traditionally in the management of epilepsy, thus supporting the appraisal of biologically active components of this plant as antiepileptic agents.